Influência de diferentes sistemas adesivos na resistência de união de pinos de fibra à dentina intrarradicular - Campos, Fernanda [UNESP]; Sarmento, Hugo Ramalho; Alves, Maria Luiza Lima; de Sousa, Rafael Santiago; de Sousa, André Rômulo Rozado; e Souza, Rodrigo Othávio de Assunção (APESB (Associacao de Apoio a Pesquisa em Saude Bucal), 2011)
Objective: To evaluate the influence of three adhesive systems on the bond strength of fiber post luted to root dentine. The hypothesis was that the bond strength is influenced by the adhesive system. Method: The canals of thirty single-root bovine roots (16mm in length) were prepared using the preparation drill (FGM) until 12mm. 14 mm of each root was embedded with acrylic resin and the specimens were allocated into three groups (n=10), considering the factor adhesive (3 levels): Gr1- Scotchbond Multipurpose Plus (3M ESPE), Gr2- One Step (Bisco) and Gr3- Excite DSC (Ivoclar Vivadent). The adhesive systems were applied using a microbrush, according to the manufacture's recommendations. The fiber posts (White Post DC, FGM) were luted with dual resin cement (All-Cem,FGM). After, the cores with composite resin (Llis, FGM) were made and each set of root/post/core was submitted to the mechanical cycling (Erios, Brazil) (10 6 cycles, 84N, 4 Hz, inclination of 45 o, 37 oC, water). Each specimen was cut in 4 samples (1.8mm in thickness), which were submitted to the push-out test in a universal testing machine (ServoPulser - Shimadzu) (50Kgf, 1mm/min). The data (MPa) were analyzed using ANOVA (1-way) and Tukey test (5%). Results: The factor adhesive (P=0.00352) influenced the bond strength significantly (ANOVA). Gr1 (6.8±3.8 MPa) a presented higher bond strength values than Gr2 (3.1±1.5 MPa) b and similar to Gr3 (4.4±3.3) a,b. Moreover, Gr3 and Gr2 were similar between them (Tukey). The hypothesis was accepted. Conclusion: Based on the results it was concluded that chemical and dual polymerization adhesive system should be used for the adhesive luting fiber post procedures.
Influence of different adhesive systems on the bond strength of fiber post to root dentin
Keywords: Cementation; Post and core technique; Resin cements